2008
DOI: 10.1002/pbc.21728
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hemorrhage in childhood immune thrombocytopenic purpura

Abstract: We retrospectively analyzed 750 patients with ITP for development of intracranial hemorrhage (ICH). Seventeen cases with age range of 10 months to 18 years were studied. Ten patients were of acute ITP and seven had chronic ITP. Nine patients developed ICH one month after the onset of ITP and five patients had ICH on presentation. ICH was precipitated by trauma in four patients and possibly the use of NSAIDs in one patient. Median platelets counts at the time of ICH were 12 x 10(9)/L (range 2-50 x 10(9)/L). Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 13 publications
3
18
0
13
Order By: Relevance
“…Similar results were reported by Japanese studies (0.45 and 0.52%) [12,13]. Other Eastern populations such as Turkey and India reported an even higher incidence of 1.2–3.3% [9,14,15], but the latter was attributed to referral bias. However, other studies reported a much lower incidence of 0.17 [3] and 0.24% [5].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were reported by Japanese studies (0.45 and 0.52%) [12,13]. Other Eastern populations such as Turkey and India reported an even higher incidence of 1.2–3.3% [9,14,15], but the latter was attributed to referral bias. However, other studies reported a much lower incidence of 0.17 [3] and 0.24% [5].…”
Section: Discussionsupporting
confidence: 83%
“…Predisposing factors, predictors and outcome of ICH in ITP have been difficult to ascertain due to the rare occurrence of this complication. ICH is a significant cause of morbidity and mortality [4] though its incidence varies from about 0.1 to 1.0% [5,6,7] up to 2% in some studies [8,9]. This study was carried out to better understand ICH in Egyptian children with ITP, including its incidence, risk factors, management and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The most significant clue in these patients is the presence of mucocutenous (wet¬-purpura) bleeding (49%). 77% of bleedings are intracranial hemorrhages (87% supratentorial) and 23% are subdural hemorrhages (1,21,22).…”
Section: History and Clinical Findingsmentioning
confidence: 99%
“…It is thought that children younger than 3 years of age and those with mucosal bleeding face a higher risk of ICH (13). Trauma and the use of nonsteroidal anti-inflammatory drugs have also been reported as precipitating factors for ICH (13,14).…”
Section: Introductionmentioning
confidence: 99%